Co-encapsulation of omega-3 and vitamin D3 in beeswax solid lipid nanoparticles to evaluate physicochemical and in vitro release properties - Shakeri, Mohammad; Ghobadi, Runak; Sohrabvandi, Sara; Khanniri, Elham; Mollakhalili-Meybodi, Neda (Frontiers in Nutrition, 2024)
In recent years, lipophilic bioactive compounds have gained much attention due to their wide range of health-benefiting effects. However, their low solubility and susceptibility to harsh conditions such as high temperatures and oxidation stress have limited their potential application for the development of functional foods and nutraceutical products in the food industry.Nanoencapsulation can help to improve the stability of hydrophobic bioactive compounds and protect these sensitive compounds during food processing conditions, thus overcoming the limitation of their pure use in food formalin buffer. The objective of this work was to co-entrap vitamin D3 (VD3) and omega 3 (ω3) as hydrophobic bioactive compounds providing significant health benefits in beeswax solid lipid nanoparticles (BW. SLNs) for the first time and to investigate the effect of different concentrations of VD3 (5 and 10 mg/ml) and ω3 (8 and 10 mg) on encapsulation efficiency (EE). Our findings revealed that the highest EE was obtained for VD3 and ω3 at concentrations of 5 mg/ml and 10 mg, respectively. VD3/ω3 loaded BW. SLNs (VD3/ω3 -BW. SLNs) were prepared with zeta potential and size of -32 mV and 63.5 nm, respectively. Results obtained by in-vitro release study indicated that VD3 release was lower compared to ω3 in the buffer solution. VD3 and ω3 incorporated in BW. SLNs demonstrated excellent stability under alkaline and acidic conditions. At highly oxidizing conditions, 96.2 and 90.4% of entrapped VD3 and ω3 remained stable in nanoparticles. Moreover, nanoparticles were stable during one month of storage, and no aggregation was observed. In conclusion, co-loaded VD3 and ω3 in BW. SLNs have the great potential to be used as bioactive compounds in food fortification and production of functional foods.